Corneal collagen crosslinking in the treatment of infectious keratitis - Anwar HM; El-Danasoury AM; Hashem AN (Clinical Ophthalmology, 2011)
Hamed Mofeez Anwar, Alaa M El-Danasoury, Ayman Nasr HashemMagrabi Eye Hospital, Jeddah, Saudi ArabiaPurpose: To report the use of corneal collagen crosslinking in the treatment of infective keratitis not responding to antimicrobial therapy.Methods: Two retrospective case reports of infective keratitis treated with corneal collagen crosslinking.Results: In both cases, corneal collagen crosslinking caused a rapid resolution of the infective keratitis, leaving residual stromal scarring. Due to the density of scarring, one case required subsequent penetrating keratoplasty for visual rehabilitation.Conclusion: Corneal collagen crosslinking is a promising new technique for the management of infective keratitis not responding to antimicrobial therapy. Further elucidation of its safety and role in management of infectious keratitis is needed by way of future studies.Keywords: CCL, riboflavin, UVA